2018
DOI: 10.1038/s41598-017-18821-w
|View full text |Cite|
|
Sign up to set email alerts
|

An engineered CARS substrate with giant field enhancement in crisscross dimer nanostructure

Abstract: We theoretically investigate the optical properties of a nanostructure consisting of the two identical and symmetrically arranged crisscrosses. A plasmonic Fano resonance is induced by a strong interplay between bright mode and dark modes, where the bright mode is due to electric dipole resonance while dark modes originate from the magnetic dipole induced by LC resonances. In this article, we find that the electric field “hotspots” corresponding to three different wavelengths can be positioned at the same spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…This results in studying interesting plasmonic properties such as a shift in plasmonic resonances, hybrid plasmon modes, sizeable local-field enhancement (hot-spot generation), etc. Numerous studies demonstrating such large field local enhancement have been reported based on various nanostructures such as dimers, nanoparticles on a metallic film, and so on [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Of these, the nanoparticles coupled with film design has attracted significant interest recently [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…This results in studying interesting plasmonic properties such as a shift in plasmonic resonances, hybrid plasmon modes, sizeable local-field enhancement (hot-spot generation), etc. Numerous studies demonstrating such large field local enhancement have been reported based on various nanostructures such as dimers, nanoparticles on a metallic film, and so on [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Of these, the nanoparticles coupled with film design has attracted significant interest recently [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to promote the application and development of SEHRS technology in different fields, it is particularly important to develop SEHRS substrates which can enhance the incident light and the scattered light in the same spatial locations. In fact, for surface enhanced nonlinear optical processes, the plasmonic substrate with multiple resonances at the same spatial locations is indispensable 23 , 24 .
Figure 1 Energy-level diagrams for Raman scattering, surface-enhanced Raman scattering, hyper-Raman scattering, and surface-enhanced hyper-Raman scattering.
…”
Section: Introductionmentioning
confidence: 99%
“…The plasmons behave like photons in conventional lasers with a plasmonic cavity which helps spaser to break the diffraction limit [ 4 , 5 ]. The near field enhancement produced by nanostructures have a vast range of applications such as sensing [ 6 ], perfect light absorption [ 7 ], switching and nanocircuits [ 8 ], light speed manipulation and dispersion [ 9 ], cloaking and imaging [ 10 ], focusing and lasing [ 11 ], enhanced non-linear effect [ 12 ], surface-enhanced Raman scattering [ 13 ] and holograms. Coherent active plasmon-based structures open paths for the expansion of SP-based applications and investigation of the matter-light interactions at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%